Perceptions of competency‐based medical education from medical student discussion forums. Issue 7 (28th January 2019) - Dehmoobad Sharifabadi, Anahita; Clarkin, Chantalle; Doja, Asif
Abstract : Background: Competency‐based medical education (CBME) is becoming widely implemented in medical education. Trainees' perceptions of CBME are important factors in the implementation and acceptance of CBME. Online discussion groups allow unique insight into trainees' perceptions of CBME during residency training. Methods: We analysed 867 posts from 20 discussion threads in Premed 101 (Canadian) and 2756 posts from 50 threads in Student Doctor Network (SDN) (American) usingNVivo 11 . Inductive content analysis was used to develop a data‐driven coding scheme that evolved throughout the analysis. Measures were taken to ensure the trustworthiness of findings, including co‐coding of a subsample of 600 posts, peer debriefing, consensus‐based analytical decision making and the maintenance of an audit trial. Results: Medical residents and students participating in the discussion forums emphasised select themes regarding the implementation of CBME in residency training. Concerns about CBME in Canada primarily involved its implications for the length of residency and post‐residency opportunities. Posts on the American forum had a prominent focus on differing areas, such as the subjectivity in the assessment of core competencies and the role of CBME in termination of a resident's position. Conclusions: Online discussion groups have the potential to provide unique insight into perceptions of CBME. The presented concerns may have implications for refining the model of CBME and illustrate the importance of providing clarification for trainees regarding length of training and evaluation structures from those involved in designing of CBME programmes. Abstract : To facilitate the further development of CBME practices, the authors analyze student discussion forums, highlighting their potential to serve as useful continuous quality improvement tools.